2017
DOI: 10.1111/febs.13999
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of the mammalian heat shock factor 1

Abstract: Living organisms are endowed with the capability to tackle various forms of cellular stress due to the presence of molecular chaperone machinery complexes that are ubiquitous throughout the cell. During conditions of proteotoxic stress, the transcription factor heat shock factor 1 (HSF1) mediates the elevation of heat shock proteins, which are crucial components of the chaperone complex machinery and function to ameliorate protein misfolding and aggregation and restore protein homeostasis. In addition, HSF1 or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
96
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 136 publications
(99 citation statements)
references
References 175 publications
2
96
1
Order By: Relevance
“…Several kinases have been implicated in phosphorylation of HSF1 at serine 307, including the MAPK kinase MEK and the p38 MAPK. Notably, among the p38 MAPK family members, p38d MAPK is particularly efficient catalyst of phosphorylation, whereas p38c MAPK is the most specific [33, 34]. Nonetheless, it remains unclear how these events regulate HSF1 activity in IPF fibroblasts.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several kinases have been implicated in phosphorylation of HSF1 at serine 307, including the MAPK kinase MEK and the p38 MAPK. Notably, among the p38 MAPK family members, p38d MAPK is particularly efficient catalyst of phosphorylation, whereas p38c MAPK is the most specific [33, 34]. Nonetheless, it remains unclear how these events regulate HSF1 activity in IPF fibroblasts.…”
Section: Discussionmentioning
confidence: 99%
“…However, it is now appreciated that increased post-transcriptional modification, induced via sumoylation, acetylation and phosphorylation can also contribute to impaired HSF1 activity. In these circumstances, it has been shown that modulation of HSF1 activity through Ser303/Ser307 phosphorylation and sumoylation at K298 are induced hyperactivity, thereby resulting in decline HSF1 transcriptional activation and increased oxidant-induced cellular damage [33, 34].…”
Section: Introductionmentioning
confidence: 99%
“…HSP70 major regulator is its transcription factor HSF1, whose activation is accompanied by its phosphorylation, being the Ser326 residue critical. With these premises, we searched for HSF1 expression in CLL B cells and we found that such as HSP70, HSF1 was also overexpressed in our patients.…”
Section: Discussionmentioning
confidence: 99%
“…In mammalian cells, HSP110, HSP90, HSP70, HSP60, HSP40, and HSP27 are expressed constitutively, but their inducible forms are products of the transcriptional 'heat stress response', which is triggered by a heat shock transcription factor 1 (HSF1) whose activation results from the denaturation of intracellular proteins after any proteotoxic exposure (see Figure 3 and [55]). In vivo, the proteotoxic effects and HSF1 activation may take place upon such pathophysiological states as hypoxia (ischemia), acidosis, inflammation, edema, and others.…”
Section: Molecular Chaperones: Localization Activities and Implicatmentioning
confidence: 99%